Comic based learning courseware for form 1 history subject / Nor Aniza Sani - Nor Aniza, Sani (2012)
Comic Based Learning Courseware is a new enhancement in education area for student who studied Form 1 History subject. However, previous researchers such as Game Based Learning Courseware were done purposely to learners who likes to play game, while this project leans towards aiding the learners who likes to read but having difficulties in understand and memorizing. The development of Comic Based Learning Courseware prototype was done using Macromedia Authorware 7.0 and utilizes multimedia content such as pictures, text, color, sound and audio as a medium for teaching. The approach that has been taken in this project is to analyze and compare student interest in learning History subject before and after using this courseware. Constructing ADDIE Model is emphasized in five steps of methodology which are analysis, design, development, implementation and evaluation. This Comic Based Learning Courseware for Form 1 History subject hopefully will contribute further in this evolving education technology .